Compartmentalization and Clonal Amplification of HIV-1 Variants in the Cerebrospinal Fluid during Primary Infection - Schnell, Gretja (American Society for Microbiology (ASM), 2010)
Human immunodeficiency virus type 1 (HIV-1)-associated dementia (HAD) is a severe neurological disease that affects a subset of HIV-1-infected individuals. Increased compartmentalization has been reported between blood and cerebrospinal fluid (CSF) HIV-1 populations in subjects with HAD, but it is still not known when compartmentalization arises during the course of infection. To assess HIV-1 genetic compartmentalization early during infection, we compared HIV-1 populations in the peripheral blood and CSF in 11 primary infection subjects, with analysis of longitudinal samples over the first 18 months for a subset of subjects. We used heteroduplex tracking assays targeting the variable regions of env and single-genome amplification and sequence analysis of the full-length env gene to identify CSF-compartmentalized variants and to examine viral genotypes within the compartmentalized populations. For most subjects, HIV-1 populations were equilibrated between the blood and CSF compartments. However, compartmentalized HIV-1 populations were detected in the CSF of three primary infection subjects, and longitudinal analysis of one subject revealed that compartmentalization during primary HIV-1 infection was resolved. Clonal amplification of specific HIV-1 variants was identified in the CSF population of one primary infection subject. Our data show that compartmentalization can occur in the central nervous system (CNS) of subjects in primary HIV-1 infection in part through persistence of the putative transmitted parental variant or via viral genetic adaptation to the CNS environment. The presence of distinct HIV-1 populations in the CSF indicates that independent HIV-1 replication can occur in the CNS, even early after HIV-1 transmission.